How to … celebrate National Receptionist Day. (2nd May 2019) - Ashurst, Adrian
Abstract : Making all staff feel appreciated is key to retaining them and running a successful business overall. This month provides an opportunity to dedicate some extra attention to the home's receptionists: Adrian Ashurst reveals how.